O Everolimo na redução do índice de massa do ventrículo esquerdo e na espessura médio intimal de carótida no transplante renal: ensaio clínico prospectivo randomizado - Garcia, Paula Dalsoglio [UNESP] (2016)
Introduction: Kidney transplantation is the gold standard treatment for end-stage renal disease. Allograft survival after one year of transplantation has had a significant improvement. However, there is a lack of improvement in patient and allograft long term survival. The mTOR inhibitors (mammalian target of rapamycin inhibitor) are the newest drugs available to prevent allograft rejection and they seem to have potential benefits in reducing myocardial hypertrophy and atherosclerosis in experimental studies. This benefits for kidney transplanted patients is still controversial. Objective: To compare the effect of everolimus to the tacrolimus in reducing left ventricular mass index (LVMi) and carotid intima-media thickness (IMT) after one year in kidney transplanted patients. Material and Methods: This randomized, open-label, controlled trial compared the effect of everolimus to tacrolimus in reducing the LVMi and the IMT in kidney transplanted patients after one year of these immunosuppressive therapies. After initial immunosuppression with tacrolimus, mycophenolate sodium (MFS) and prednisone (PDN), patients were randomly assigned at 12±4 weeks in a 1:1 ratio to undergo conversion from tacrolimus to everolimus (EVERO group) and maintenance of MFS and PDN or continue on standard tacrolimus-based treatment (TACRO group). Each patient was randomized only after a kidney biopsy with no evidence of rejection or inflammation. Clinical and laboratorial data were collected on randomization day and 3, 6, 9, and 12 months after randomization. Echocardiograms were done at the randomization and 6 and 12 months after. Results: Everolimus significantly reduced IMT after one year (p=0,012), despite higher levels of proteinuria and cholesterol. The percentage of reduction of the IMT on the EVERO group was almost twice the reduction of the TACRO group (p=0,0528). No difference was found on the reduction of LVMi between groups. The renal function was excellent in both groups at one year, with no superiority of any drug. Everolimo may contribute to the reduction of cardiovascular mortality of this population in long term. Conclusion: Everolimus reduced IMT at one year in kidney transplanted patients. No difference between groups was found in the reduction of iMVE or increase on renal function in the end of the study.